Burnout dan Work-Life Balance pada Dosen Wanita di Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Karima, Ulya (Fakultas Dakwah UIN KHAS Jember, 2023)
Burnout is defined as a manifestation of the mismatch between the life being lived. Previous research has revealed that achieving work-life balance among employees will have an impact on work engagement. The focus of this research is whether there is a relationship between burnout and work-life balance among female lecturers at the State Islamic University Kiai Haji Achmad Siddiq Jember. This study aims to determine the relationship between burnout and work-life balance among female lecturers at UIN KHAS Jember. A correlational quantitative method was used with sample selection based on simple random sampling technique. The population in this study was 126 individuals, so the sample size was 56 female lecturers at the State Islamic University Kiai Haji Achmad Siddiq Jember. Based on the Pearson correlation analysis, it was found that p = 0.000 < 0.05, indicating a significant correlation between burnout and work-life balance. Furthermore, from the Pearson correlation results, it is known that the relationship is negative. This means that the higher the level of burnout, the lower the level of work-life balance, and vice versa.